2017
DOI: 10.1002/chem.201605514
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Reactive Cyclopropane Intermediate via a Unique Catalyst‐Free Spontaneous Cyclopropanation Step at 0 °C

Abstract: A remarkably mild, catalyst-free cyclopropanation reaction is confirmed by low-temperature isolation of a fused bicyclic cyclopropane intermediate. This intermediate is one of two that were isolated and fully characterised in a three-step temperature-controllable reaction cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It likely results from the overreduction of 2-Et 2 O , followed by C–H activation by the anionic Be­(I) center of one C2-methyl substituent at the carbene center to form the fused cyclopropane ring, and finally addition of the anionic Be–H moiety to the C carbene –N bond of the CAAC ligand, leading to the six-membered C 4 BeN ring. This kind of CAAC ring expansion has been observed with CAAC-stabilized boranes and low-valent boron compounds, while the spontaneous cyclopropanation by C2-methyl C–H activation has been reported upon adduct formation of CAAC with 2-mesityl-1- tert -butyliminoborane . In contrast, the twofold reduction of [(CAAC)­MgCl 2 ] in the presence of another equivalent of CAAC resulted in the rearrangement of one CAAC ligand to a cyclobutanimine, into which the Mg center inserts to give a C 4 Mg metallacycle with a pendant imine functionality .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It likely results from the overreduction of 2-Et 2 O , followed by C–H activation by the anionic Be­(I) center of one C2-methyl substituent at the carbene center to form the fused cyclopropane ring, and finally addition of the anionic Be–H moiety to the C carbene –N bond of the CAAC ligand, leading to the six-membered C 4 BeN ring. This kind of CAAC ring expansion has been observed with CAAC-stabilized boranes and low-valent boron compounds, while the spontaneous cyclopropanation by C2-methyl C–H activation has been reported upon adduct formation of CAAC with 2-mesityl-1- tert -butyliminoborane . In contrast, the twofold reduction of [(CAAC)­MgCl 2 ] in the presence of another equivalent of CAAC resulted in the rearrangement of one CAAC ligand to a cyclobutanimine, into which the Mg center inserts to give a C 4 Mg metallacycle with a pendant imine functionality .…”
Section: Resultsmentioning
confidence: 89%
“…This kind of CAAC ring expansion has been observed with CAAC-stabilized boranes and low-valent boron compounds, 41−43 while the spontaneous cyclopropanation by C2methyl C−H activation has been reported upon adduct formation of CAAC with 2-mesityl-1-tert-butyliminoborane. 44 In contrast, the twofold reduction of [(CAAC)MgCl 2 ] in the presence of another equivalent of CAAC resulted in the rearrangement of one CAAC ligand to a cyclobutanimine, into which the Mg center inserts to give a C 4 Mg metallacycle with a pendant imine functionality. 45 The 9 Be NMR shift of 3 at 17.4 ppm (fwmh ≈ 257 Hz) is consistent with a trialkylberyllate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Braunschweig et al reported an unusual C–H addition of an unsaturated NHC's backbone to a BN bond of an iminoborane, affording a borylated carbene. 6 The Braunschweig group also reported C–H addition of acetone across BN triple bond and across BB of an NHC-ligated diboryne. 7 Schulz and co-workers also reported the enolization of ketones by a gallium phosphinidene.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, BN-containing compounds have attracted tremendous attention, as the replacement of CC with BN bonds has turned out to be an ingenious strategy to create novel molecules featuring unique chemical and physical properties. A variety of iminoboranes have been synthesized, allowing the expansion of the reactivity patterns over the past half century, including adduct formation, cycloaddition with MC, EC (E = O, S, Se), CC, and RN 3 , and polar bond addition. ,,, Very recently, the Kong group reported boraiminolithium, which displayed potential in the synthesis of N-functionalized iminoboranes . However, the variation of substituents on the boron site is still of great challenge, and the scope of B-substituents is limited to alkyl, aryl, amino, silyl groups, and transition-metal fragments (Figure a).…”
Section: Introductionmentioning
confidence: 99%